2021
DOI: 10.1002/bdr2.1879
|View full text |Cite
|
Sign up to set email alerts
|

Causes of neonatal and postneonatal death among infants with birth defects in Texas

Abstract: Background: The proportion of deaths attributed to various causes has not been quantified among infants with birth defects. We sought to describe the causes of neonatal and postneonatal death among infants in the Texas Birth Defects Registry. Methods: We calculated frequencies and percentages for both underlying causes and all causes (underlying or contributing) of neonatal (0-27 days) and postneonatal (28-364 days) death listed on death certificates among infants born alive with birth defects and delivered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…We found the lowest infant survival was among infants with severe microcephaly and with co‐occurring chromosomal/syndromic associations (66.1%), followed by infants with co‐occurring multiple defects (85.8%). Benjamin et al (2021) also observed lower infant survival (83.8%) among infants with syndromic birth defects relative to infants with isolated birth defects. Sattolo et al (2022) described a correlation between multiple birth defects and higher mortality.…”
Section: Discussionmentioning
confidence: 93%
“…We found the lowest infant survival was among infants with severe microcephaly and with co‐occurring chromosomal/syndromic associations (66.1%), followed by infants with co‐occurring multiple defects (85.8%). Benjamin et al (2021) also observed lower infant survival (83.8%) among infants with syndromic birth defects relative to infants with isolated birth defects. Sattolo et al (2022) described a correlation between multiple birth defects and higher mortality.…”
Section: Discussionmentioning
confidence: 93%
“…In Texas, a study of 8000 infants with birth defects found that deaths owing to circulatory, respiratory, and digestive causes were frequent before 1 year of age. 19 In another study of children with birth defects, circulatory disorders ranked as an important cause of death before age 10 years. 6 Circulatory disorders are common in children with heart defects, diaphragmatic hernia, and lung hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…6 Circulatory disorders are common in children with heart defects, diaphragmatic hernia, and lung hypoplasia. 19 Infections such as respiratory syncytial virus can be common in children with spina bifida, lung malformations, cleft palate, and biliary atresia. 20 Prematurity can also exacerbate risks of mortality because of circulatory, respiratory, and digestive complications, 17,19,21 although birth defects were associated with these causes even when we excluded preterm births.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations